Analisis Peran Hukum Siber dalam Menjaga Privasi Pengguna di Indonesia pada Era Digital - Johanes Maruli Burju (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
In the ever-evolving digital era, the importance of cyber law in safeguarding user privacy cannot be overstated. As a distinct legal discipline, cyber law examines regulations that oversee activities in cyberspace, offering legal protection regarding personal data and user privacy. Referring to various credible sources, this article evaluates the role of cyber law in protecting user privacy in the Indonesian context. The article discusses regulations such as the Electronic Information and Transactions Law (UU ITE), the Government Regulation on Electronic Systems, and the Personal Data Protection Bill. The main elements analyzed include supervision, regulation, resolution, and protection of user rights when facing digital security challenges. The examination shows that cyber law plays a significant role in protecting individuals' personal information, thereby encouraging safer and more trustworthy digital services. Furthermore, the article points out the various challenges faced in enforcing cyber law, such as administrative constraints, inadequate digital literacy, and limited access to justice, especially for those without legal knowledge or support. Consequently, to improve the effectiveness of cyber law, continued efforts are needed to strengthen the digital regulatory framework and provide more comprehensive user privacy protection. This perspective seeks to enhance understanding of the significance of cyber law in safeguarding privacy and proposes recommendations for governments and relevant organizations in addressing privacy issues in the digital age.